Teachers' Accuracy in Estimating Social Inclusion of Students With and Without Special Educational Needs - Wilbert, Jürgen; Urton, Karolina; Krull, Johanna; Kulawiak, Pawel R.; Schwalbe, Anja; Hennemann, Thomas (Frontiers in Education, 2020)
It is unclear to what extent teachers can accurately assess the social inclusion of their students with and without SEN. The study aims to shed light on these desiderata. Students (N = 1.644) with SEN (learning, behavior, and language problems) and without SEN and their teachers (N = 79) participated in the study. Sociometric peer nominations, students' self-perceived social inclusion, and teachers' assessments regarding students' social inclusion and self-perceived social inclusion were administered. The results suggest that teachers are moderately accurate in identifying social acceptance and social rejection, while accuracy is low when assessing students' self-perceived social inclusion. That said, rating accuracy varied strongly between teachers, ranging from no agreement to a perfect concordance. Teachers seem to be more accurate in estimating the social acceptance of students with learning problems. The results emphasize the importance of differentiating between various social inclusion criteria (i.e., students' self-report vs. peer nominations) and accounting for inter-individual differences in teachers' rating accuracy.